(NsINTEZ CEOLITOW S RAZNOZARQDNYMI KATIONAMI (B:s [(NsBORNIK STATEJ(B] /s - (NlAPERA[WILI(B, (Nl(B.(Nq(B.s; (NiN(B-(NT FIZI^ESKOJ I ORGANI^ESKOJ HIMII IM(B. (Np(B.(Ng(B. (NmELIKI[WILIs ((NtBILISI (B:s (NmECNIEREBA(B,s, 1986)
(NbIBLIOGR(B. (NW KONCE ST(B.s
Keywords: (NsINTEZs; (NcEOLITYs